2012
DOI: 10.1177/1049731512467072
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Evidence-Based Practice

Abstract: The article reports on the findings of a review of empirical studies examining the implementation of evidence-based practice (EBP) in the human services. Eleven studies were located that defined EBP as a research-informed, clinical decision-making process and identified barriers and facilitators to EBP implementation. A thematic analysis of the findings of the 11 studies produced a list of barriers to EBP implementation grouped in terms of inadequate agency resources dedicated to EBP; skills and knowledge of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(40 citation statements)
references
References 42 publications
1
37
0
2
Order By: Relevance
“…The evidence-based practice process requires that practitioners or organizations: 1) form an answerable question; 2) seek the best evidence to answer that question; 3) critically appraising the evidence; 4) integrate that appraisal with their clinical expertise, client values, preferences, and clinical circumstances; and 5) evaluate the outcome (Gibbs, 2003). A helpful example of the application of this process has been published in this journal (McCracken & Marsh, 2008), and a recent review identified a number of studies that evaluated efforts to implement the evidence-based practice process in community settings (Gray, Joy, Plath, & Webb, 2012). The direct application of ESIs, which is the focus of our review, involves integrating interventions that have some evidence for their efficacy and effectiveness for a given population or clinical problem into routine care settings.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence-based practice process requires that practitioners or organizations: 1) form an answerable question; 2) seek the best evidence to answer that question; 3) critically appraising the evidence; 4) integrate that appraisal with their clinical expertise, client values, preferences, and clinical circumstances; and 5) evaluate the outcome (Gibbs, 2003). A helpful example of the application of this process has been published in this journal (McCracken & Marsh, 2008), and a recent review identified a number of studies that evaluated efforts to implement the evidence-based practice process in community settings (Gray, Joy, Plath, & Webb, 2012). The direct application of ESIs, which is the focus of our review, involves integrating interventions that have some evidence for their efficacy and effectiveness for a given population or clinical problem into routine care settings.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing the importance of research evidence for improving organizational performance and service outcomes, policymakers in many countries have made evidence-informed health and human services a priority [7, 8]. In the USA, an increasing number of state and local governments now link the use of research evidence regarding “effective” programs and practices, including evidence-based treatments (EBTs), to funding decisions or service reimbursement [9].…”
Section: Introductionmentioning
confidence: 99%
“…Challenges to the use of research evidence, and particularly to the adoption, implementation, and sustainment of EBTs, are well documented [8, 22, 23]. Less studied are the formal supports—i.e., staff positions, infrastructural supports, and special initiatives—organizations may put in place to help overcome these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research and debate within this discourse has primarily focused on the travelling of knowledge from research to practice and vice versa, as well as on the utilization of research-based knowledge in fields of practice, its preconditions and outcomes (Cnaan & Dichter, 2008;Gira, Kessler, & Poertner, 2004;Gray et al, 2013;Gredig & Sommerfeld, 2008;Johansson, 2009;Mullen, Bledsoe, & Bellamy, 2008;Osterling & Austin, 2008). Issues of international, cross-country and 'cross-context' exchange of knowledge have often been overlooked.…”
Section: International Travelling Of Concepts and Programmesmentioning
confidence: 97%